Statistical Study of Sustainable Development Goals Indicators in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The Sustainable Development Goals cover a broad range of social and economic issues, including poverty eradication, education, gender equality, clean water and sanitation, energy, economic growth, and sustainable cities. The environmental goals address climate change, biodiversity conservation, and sustainable consumption and production. The Sustainable Development Goals require cooperation not only between states, but also between the public, private sector, and non-governmental organizations. Achieving these goals requires the international community to unite, support each other, and embrace innovation as a driving force.